Lactobacillus plantarum as Biopreservative Agent in Paneer for Dietary Food of Diabetic and Coronary Heart Disease Patients - Marlia Singgih; Kanaka L. Ahsogan; Irma M. Puspitasari; Sophi Damayanti (Indonesian Journal of Clinical Pharmacy, 2017)
Paneer is a food product that is obtained by heating milk followed by acid coagulation. It is known as a diet food that is recommended for diabetic and coronary heart disease patients. A relatively shorter shelf life of paneer is considered to be a major hurdle in its production. The present preliminary study was conducted to determine antibacterial activity of Lactobacillus plantarum against Eschericia coli and Bacillus cereus, to develop it as biopreservative agent in paneer before using it for dietary food of diabetic and coronary heart disease patients in next clinical study. The antibacterial activities were tested through Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) using microdilution well method. Biopreservative activity in paneer was tested using total plate count method based on time and temperature variations. Result showed that Lactobacillus plantarum inhibited Bacillus cereus and Eschericia coli with MIC of 3125 and 1562.5 µg/mL whereas MBC was in a value of >6250 and >3125 µg/mL, respectively. As a biopreservative agent, addition of Lactobacillus plantarum to paneer showed no bacterial growth until 7 days in room temperature and 9th day in cold temperature. It is concluded that Lactobacillus plantarum could be used as a natural biopreservative agent for extending the shelf life of paneer. The paneer with addition of Lactobacillus plantarum as biopreservative will then be consumed by diabetic patient and coronary heart patients in next clinical study.Keywords: Biopreservative, Lactobacillus plantarum, MBC, MIC, paneer Lactobacillus plantarum sebagai Biopreservatif pada Paneer untuk Makanan Diet Pasien Diabetes dan Jantung KoronerAbstrak Paneer adalah produk makanan yang diperoleh dengan pemanasan susu diikuti dengan koagulasi asam. Paneer dikenal sebagai makanan diet yang direkomendasikan untuk pasien dengan penyakit diabetes dan penyakit jantung koroner. Paneer memiliki ketahanan yang relatif lebih pendek sehingga dianggap menjadi masalah utama dalam produksi. Penelitian pendahuluan ini dilakukan untuk mengetahui aktivitas antibakteri Lactobacillus plantarum terhadap Eschericia coli dan Bacillus cereus, untuk mengembangkannya sebagai biopreservatif sebelum digunakan sebagai makanan diet pasien dengan penyakit diabetes dan penyakit jantung koroner pada uji klinik. Pengujian antibakteri diuji melalui Minimum Inhibitory Concentration (MIC) dan Minimum Bactericidal Concentration (MBC) menggunakan mikrodilusi metode susia. Selanjutnya, pengembangan sebagai biopreservatif pada paneer diuji menggunakan metode angka lempeng total berdasarkan waktu dan variasi suhu. Hasil penelitian menunjukkan bahwa Lactobacillus plantarum menghambat Bacillus cereus dan Eschericia coli dengan MIC 3125 dan 1562,5 µg/mL sedangkan nilai MBC masing-masing adalah 6250 dan 3125 µg/mL. Sebagai biopreservatif, penambahan Lactobacillus plantarum untuk paneer tidak menunjukkan pertumbuhan bakteri sampai 7 hari pada suhu kamar dan hari ke-9 di dalam lemari pendingin. Kesimpulannya, Lactobacillus plantarum dapat digunakan sebagai agen biopreservatif alami untuk memperpanjang masa simpan paneer yang akan dikonsumsi untuk pasien dengan penyakit diabetes dan penyakit jantung koroner pada tahap uji klinik.Kata kunci: Biopreservatif, Lactobacillus plantarum, MBC, MIC, paneer